HUBUNGAN ANTARA DERAJAT KEPARAHAN MALARIA DENGAN JUMLAH TROMBOSIT PADA PASIEN MALARIA DI RSU BETHESDA SERUKAM KABUPATEN BENGKAYANG PERIODE 2009 2012 - ., Ivanna (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Malaria is a parasitic haematological infectious diseasewhich could influence platelet count on the infected patient. Some studiesstated that platelet was involved in severe malaria pathogenesis. BethesdaSerukam Hospital is located in Bengkayang, the endemic site of malaria.Objective: The objective of this research was to find relationship betweenthe severity of malaria(severe malaria and uncomplicated malaria)withplatelet count. Method: This research was an analytic observational studywith cross sectional approach. The data were collected from medical recordof the patients at Bethesda Serukam Hospital. The information collectedfrom data were malaria diagnosis and platelet count of 125 malaria patients.Then the data were analyzed by using Chi-Square test. Result: Thisresearch found that 33(26,4%)malaria patients had low platelet count and23(18,4%)malaria patients had severe malaria complication. There was asignificant relationship between the severity of malaria with platelet count(p = 0,000). And based on the malaria species, there were a significantrelationship between severity of malaria caused by falciparum malaria(p= 0,001)and mixed infection(p = 0,048)with platelet count. Conclusion:The low platelet count is a common finding in severe malaria patient atBengkayang. The low platelet count was significantly associated withsevere malaria, especially severe falciparum malaria.Keyword: malaria, severe malaria, platelet count1)Medical School, Faculty of Medicine, Tanjungpura University, Pontianak,West Borneo2)Department of Community Medicine, Medical School, Faculty ofMedicine, Tanjungpura University, Pontianak, West Borneo3)Department of Parasitology, Medical School, Faculty of Medicine,Tanjungpura University, Pontianak, West Borneo